Pre-hospital Prognostic Factors of Out-of-Hospital Cardiac Arrest: The Difference Between Pediatric and Adult - Cheng, Fu-Jen; Wu, Wei-Ting; Hung, Shih-Chiang; Ho, Yu-Ni; Tsai, Ming-Ta; Chiu, I-Min; Wu, Kuan-Han (Frontiers in Pediatrics, 2021)
The prognosis of out-of-hospital cardiac arrest (OHCA) is very poor. Although several prehospital factors are associated with survival, the different association of prehospital factors with OHCA outcomes in pediatric and adult groups remain unclear. To assess the association of prehospital factors with OHCA outcomes among pediatric and adult groups, a retrospective observational study was conducted using the emergency medical service (EMS) database in Kaohsiung from January 2015 to December 2019. Prehospital factors, underlying diseases, and OHCA outcomes were collected for the pediatric (Age≦20) and adult groups. Kaplan-Meier type plots and multivariable logistic regression were used to analyze the association between prehospital factors and outcomes. In total, 7461 OHCAs were analyzed. After adjusting for EMS response time, bystander CPR, attended by EMT-P, witness, and prehospital defibrillation, we found that age (odds ratio [OR] = 0.877, 95% confidence interval [CI]: 0.764–0.990, p=0.033), public location (OR = 7.681, 95% CI: 1.975–33.428, p=0.003), and advanced airway management (AAM) (OR = 8.952; 95% CI, 1.414–66.081; p=0.02) were significantly associated with survival till hospital discharge in pediatric OHCAs. The results of Kaplan-Meier type plots with log-rank test showed a significant difference between the pediatric and adult groups in survival for 2 h (p<0.001), 24 h (p<0.001), hospital discharge (p<0.001), and favorable neurologic outcome (p<0.001). AAM was associated with improved survival for 2 h (p=0.015), 24 h (p=0.023), and neurologic outcome (p=0.018) only in the pediatric group. There were variations in prognostic factors between pediatric and adult patients with OHCA. The prognosis of the pediatric group was better than that of the adult group. Furthermore, AAM was independently associated with outcomes in pediatric patients, but not in adult patients. Age and public location of OHCA were independently associated with survival till hospital discharge in both pediatric and adult patients.